Kampung Sayur untuk Pengembangan Desa Wisata Kelurahan Gading Surabaya - Susi Hardjati; Syanindita Aurelya Ayu Widya Savitri (Faculty of Law, 2022)
Abstract Student Study Service is a program that must be followed by students. Through the KKNT MBKM with the village tourism scheme, students are required to help the community to explore the tourism potential in their environment so that it is more beneficial for the surrounding community. The potential of the village tourism in Gading Sub-District is Kampung Sayur (Vegetable Village) where students are on duty to help the community to explore the potential of Kampung Sayur by developing Hydroponic and Aeroponic as Appropriate Technologies that is specifically suit the conditions of the community and the environment of Gading Sub-District. Several work programs initiated by students that is contains some steps such as survey, implementation, and evaluation so that the results of the output can be monitored optimally and can be beneficial for Gading Sub-district's community. Keywords: Village Tourism; Student Study Service; Gading Sub-District; Kampung Sayur.